'9th May 2017 is OUR DAY': The Homeland Study Group Foundation and contested national imaginaries in postindependence Ghana. Issue 2 (26th January 2022) - Adotey, Edem
Abstract: Ghana has been held up as an oasis of stability in a highly volatile region of Africa due to its peaceful decolonisation process, absence of serious civil conflict and successful change of governments. However, in Ghana as in parts of postindependence Africa, there are lingering secessionist movements that are a legacy of colonialism. The latest comes from the Homeland Study Group Foundation (HSGF) which declared the former British Togoland, a former United Nations trust territory administered by the United Kingdom, as an independent state called Western Togoland. Through the prism of competing or alternative national imaginaries rather than the weak and dysfunctional state paradigm, this article seeks to explain the roots of a form of Togoland nationalism in Ghana in events of 1956 that remains relevant today. The paper argues that an apparently successful integration can stimulate/give sustenance to alternative nationalist imaginaries.